2021
DOI: 10.1111/mpp.13046
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated control of the type IV pili and c‐di‐GMP‐dependent antifungal antibiotic production in Lysobacter by the response regulator PilR

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Two-component systems have gained considerable attention due to their role in modulating a plethora of virulence mechanisms and multidrug resistance. In A. baumannii these systems include: BfmRS, which is involved in fitness, capsule production and biofilm formation; AdeRS, which regulates an efflux pump associated with antibiotic resistance; GacSA, which is involved with regulating the phenyl acetic acid catabolic pathway as well as attenuated virulence in a mouse infection model; the BaeSR system, which modulates efflux pumps and has been implicated in cross talk with the AdeRS systems, and the PmrAB system, which is involved in colistin resistance [ 4 , 5 , 26 , 66 , 78 ]. In this study the diverse nature of these systems was explored through the uncharacterized TCS, StkSR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-component systems have gained considerable attention due to their role in modulating a plethora of virulence mechanisms and multidrug resistance. In A. baumannii these systems include: BfmRS, which is involved in fitness, capsule production and biofilm formation; AdeRS, which regulates an efflux pump associated with antibiotic resistance; GacSA, which is involved with regulating the phenyl acetic acid catabolic pathway as well as attenuated virulence in a mouse infection model; the BaeSR system, which modulates efflux pumps and has been implicated in cross talk with the AdeRS systems, and the PmrAB system, which is involved in colistin resistance [ 4 , 5 , 26 , 66 , 78 ]. In this study the diverse nature of these systems was explored through the uncharacterized TCS, StkSR.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative bioinformatics analysis of the genes encoding potential response regulator proteins in the WT 04117201 A. baumannii strain identified five TCS that are absent from the avirulent A. baumannii strain SDF and therefore are hypothesized to affect virulence potential ( Table 2 ). These systems included two orphan response regulators, NasT and RsbU, and two previously characterized response regulators, AdeR, which is associated with efflux pump regulation, and BarA, coordinating the control of type IV pili [ 24 , 66 ]. The novel hybrid TCS named here as StkSR was chosen for further phenotypic investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Most environmental and intracellular factors that control cellular c-di-GMP levels in L. enzymogenes remain to be deciphered, however, enzymes important for the c-di-GMP-dependent HSAF production have been identified (Ren et al, 2020). One DGC, LchD, has already been mentioned as the subject of PilR repression (Xu et al, 2021b). Clp interacts with LchD directly and stimulates its DGC activity (Fig.…”
Section: Regulation Of Hsaf Biosynthesismentioning
confidence: 99%
“…The gene expression and promoter–reporter analyses revealed that HSAF production is controlled primarily at the gene expression level (Chen et al ., 2017). Six transcription regulators that affect the expression of the HSAF biosynthesis operon have been identified so far, including five positive regulators, PilR, Clp, LysR, LarR and CdgL, and one negative regulator, LetR (Wang et al ., 2014; Chen et al ., 2017; Su et al ., 2017; Wang et al ., 2017; Su et al ., 2018; Xu et al ., 2018; Han et al ., 2020; Xu et al ., 2021b). Clp, LysR, LarR and LetR are transcription factors that directly bind to the promoter of the HSAF biosynthesis operson (Fig.…”
Section: Hsaf the Long‐range Antifungal Weapon Of L Enzymogenesmentioning
confidence: 99%
See 1 more Smart Citation